Food preference acquired by social transmission is altered by the absence of the olfactory marker protein in mice - de Vallière, Aurélie; Lopes, Ana Catarina; Addorisio, Andrea; Gilliand, Noah; Nenniger Tosato, Monique; Wood, Dean; Brechbühl, Julien; Broillet, Marie-Christine (Frontiers in Nutrition, 2022)
Food preference is conserved from the most primitive organisms to social animals including humans. A continuous integration of olfactory cues present both in food and in the different environmental and physiological contexts favors the intake of a given source of food or its avoidance. Remarkably, in mice, food preference can also be acquired by olfactory communication in-between conspecifics, a behavior known as the social transmission of food preference (STFP). STFP occurs when a mouse sniffs the breath of a conspecific who has previously eaten a novel food emitting specific odorants and will then develop a preference for this never encountered food. The efficient discrimination of odorants is performed by olfactory sensory neurons (OSNs). It is essential and supports many of the decision-making processes. Here, we found that the olfactory marker protein (OMP), an enigmatic protein ubiquitously expressed in all mature olfactory neurons, is involved in the fine regulation of OSNs basal activity that directly impacts the odorant discrimination ability. Using a previously described Omp null mouse model, we noticed that although odorants and their hedonic-associated values were still perceived by these mice, compensatory behaviors such as a higher number of sniffing events were displayed both in the discrimination of complex odorant signatures and in social-related contexts. As a consequence, we found that the ability to differentiate the olfactory messages carried by individuals such as those implicated in the social transmission of food preference were significantly compromised in Omp null mice. Thus, our results not only give new insights into the role of OMP in the fine discrimination of odorants but also reinforce the fundamental implication of a functional olfactory system for food decision-making.